The Influence of Management Accounting Information System Characteristics on Managerial Performance in Bandung City MSMEs in 2023 - Rachman, Andry Arifian; Ikram, Syafrizal; Fadjar, Achmad (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
A country can develop with the support of various parties (government and stakeholders) and the business sector. The government makes rules and supports to protect and ensure the development of the business sector in the midst of an open business climate. Companies from abroad can operate in the country and will certainly be a challenge for entrepreneurs. So that business competition will be tighter, including competition for Micro, Small and Medium Enterprises (MSMEs). This study aims to examine the effect of Management Accounting Information System Characteristics on Managerial Performance in MSMEs in Bandung City in 2023. The research population is MSMEs in Bandung City with a research sample of 35 MSMEs. The results of the study prove that the characteristics of the Management Accounting Information System have a positive effect on Managerial Performance.